Decision Support Systems XII: Decision Support Addressing Modern Industry, Business, and Societal Needs 8th International Conference on Decision Support System Technology, ICDSST 2022, Thessaloniki, Greece, May 23-25, 2022, Proceedings - Cabral Seixas Costa, Ana Paula; Papathanasiou, Jason; Jayawickrama, Uchitha; Kamissoko, Daouda (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book constitutes the proceedings of the 8th International Conference on Decision Support Systems Technologies, ICDSST 2022, held during May 23-25, 2022. The EWG-DSS series of International Conference on Decision Support System Technology (ICDSST) is planned to consolidate the tradition of annual events organized by the EWG-DSS in offering a platform for European and international DSS communities, comprising the academic and industrial sectors, to present state-of-the-art DSS research and developments, to discuss current challenges that surround decision-making processes, to exchange ideas about realistic and innovative solutions, and to co-develop potential business opportunities. The main aim of this year's conference is to investigate the role DSS and related technologies can play in mitigating the impact of pandemics and post-crisis recovery. The 15 papers presented in this volume were carefully reviewed and selected from 46 submissions. They were organized in topical sections as follows: decision support addressing modern industry; decision support addressing business and societal needs, and multiple criteria approaches. .
Decision Support addressing modern Industry -- Blockchain Technology Potential to Transform Global Value Chains -- Predicting the Rating of an App Beyond its Functionalities: Introducing the App Publication Strategy -- Improving Machine Self-Diagnosis with an Instance-Based Selector for Real-Time Anomaly Detection Algorithms -- Blockchain and Machine Learning in Real Estate -- Modelling the Development and Deployment of Decentralized Applications in Ethereum Blockchain: A BPMN-based approach -- Decision Support addressing Business and Societal needs -- Strengthening EU Resilience: Labor Market Integration as a criterion for Refugee Relocation -- Towards an Inclusive Europe: Ranking European Countries Based on Social Sustainability Indicators -- Decision Support Ecosystems: Definition and Platform Architecture -- A systematic research methodology for business model decision making in commercialising innovative healthcare diagnostic technologies -- A DSS based on a control tower for supply chain risks management -- Multiple Criteria Approaches -- Using the FITradeoff Method for solving a truck acquisition problem at a midsize carrier -- Maturity assessment in the context of industry 4.0 - an application using FITradeoff method in a textile industry -- Sustainable Mobility Engagement and Co-planning; a Multicriteria Analysis based Transferability Guide -- A DSS for the multi-criteria vehicle routing problem with pickup and delivery and 3d constraints -- A multicriteria tool to support decision-making in the early stages of energy efficiency investments.
Keywords: Information technology-Management.; Operations research; Business information services; Blockchains (Databases).; Artificial intelligence; Computer Application in Administrative Data Processing; Operations Research and Decision Theory; IT in Business; Blockchain; Artificial Intelligence